Effect of living environment on ear, nose and throat diseases: a cross sectional survey in rural areas of Rohtas district in Bihar - Kumar, Sujeet; Aslami, Ahmad Nadeem; Rai, Tarkeshwar; Alwa, Bhaskar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Ear, nose and throat (ENT) diseases are very common in general population. Internal living environment can act an important risk factor for these diseases. In rural areas, patients do not consult ENT experts. So, free health camps can bring treatment facilities at their doorsteps. The objective of this study was to determine the pattern and prevalence of ENT diseases in rural areas of Sasaram, Rohats district, Bihar and to find out the effect of living environment on these diseases. Methods: The study was conducted using camp approach in rural areas of Sasaram, Rohtas, Bihar. ENT and Community Medicine experts, interns along with audiologists, medico social workers, nurses and paramedical staff were voluntarily involved. The patients were screened and referred to ENT experts. A logistic regression analysis was conducted to determine the internal environment factors associated with ENT diseases. Results: Out of 832 patients, 61.9% were suffering from ENT disorders. Most common age group affected was of 31-40 years. 54.8% of patients were suffering from ear diseases while nasal and throat problem was seen in 14.9% and 30.3% respectively. Multiple logistic regression analysis of living environment conditions propounds that non-availability of cross ventilation in houses and overcrowding are most important factor influencing ENT diseases. Conclusions: Free health camps conducted by medical experts act as an opportunity to screen people with various diseases of ENT in a community. Bad internal environment can act as a vital determinant for these diseases.